KOMUNIKASI AMONG DALAM TINDAK TUTUR PEMBELAJARAN - Heri Siwignyo (LITERA, 2011)
This study aims to describe and explain among (caring) communication represented by learning speech acts. The among communication in learning speech acts is a natural phenomenon of language use in a socio-cultural context. This was a qualitative study employing pragmatics and ethnography. Based on the data analysis, three categories of findings are obtained. First, the front speech act leads and controls the communication. Second, the middle speech act guides and encourages the communication. Third, the back speech act lets the communication be free. These represent the children’s among communication in the front, the peers’ among communication in the middle, and the adults’ among communication in the back; they are figurative, motivating, and delegating in nature.